Sensory test evaluation of new developed catfish fish ball/ Nina Keterina Hashim ... [et al.] - Hashim, Nina Keterina; Abdul Wahab, Nurul'Awatif; Zakaria, Fatin Nadzirah; Dasiman, Razif; Yusof, Suzana (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Catfish fish ball is still new in the Malaysia market. People's acceptance towards new product is important before the product can be marketed. The aim of this research is to determine the people acceptance towards catfish fish ball as well to determine its shelf life stored at -2 to -4 0C. The fish ball has been developed from Clarias batrachus (catfish) with three different kinds of vegetables such Solanum licopersicum (tomatoes), Brassica oleracea (broccoli) and Spinachia oleracea (spinach). The determination of people acceptance and shelf life were obtained through sensory evaluation. The sensory evaluation was scored according to the 7-point hedonic scale for flavor, color, texture, odor, appearance and overall acceptance by the 25 panelists among the students UiTM Selangor Puncak Alam Campus. The results for first and third sensory evaluation for all attributes between catfish fish ball with commercialized fish ball has significant difference at p<0.05. However, there were no significant difference between the samples at p> 0.05 during second sensory evaluation for color and appearance attributes. For the shelf life, the catfish fish ball is not significantly difference between after the production and after 3 months of production as the p-value was 0.610 (p>0.05). The mean value shown this catfish fish ball accepted as most of the sensory attribute scored more than 4 which is the cut-off point of acceptance. On the other hand, people more likely to accept the commercialized fish ball as scored obtained is 5 in almost attributes during first, second and third sensory evaluation. Meanwhile, the shelf life of this catfish fish ball can be stored at -2 0C up to 3 months.